Verificación del método analítico de espectroscopia de absorción atómica con horno de grafito para la cuantificación de cadmio en almendra de cacao (Theobroma cacao). - Araujo Abad, Lourdes Salomé (2016)
The objective of this work was to verify the performance parameters of the analytical method of atomic absorption spectroscopy with graphite furnace for quantification of cadmium in cocoa (Theobroma cacao) almond, for which a protocol was prepared, analyzes were performed on the certified reference material (MRC), the concentration of cadmium in dry cocoa beans four farms (Farm A, B, C and D) located in the cocoa zone of the country, Flavio Alfaro Manabí, was determined and an interlaboratory test was performed. The protocol (PEE / B / 14) is a standard operating procedure for the application of this method in the analysis of cadmium in cocoa almond samples. four parameters on MRC (Code. 07206B and Code. 07167A) were verified: linearity, precision, accuracy and uncertainty according to international standards (Eurachem, 2016 and IRAM 2010); thus, the linear range was set between 0 and 8 ppb, with a coefficient of R2=0.9988 linear regression; the standard deviation was 0.0005 and 0.0022 respectively; the slant was 0.007 and the recovery rate 109.75; the standard uncertainty was 0.00013 and 0.00082; which shows the reliability of the results obtained by the application of this analytical method. The cadmium content in the samples was 0.54 ppm at Farm A, 0.26 ppm Farms B-D and 0.15 ppm in the estate C. In the interlaboratory comparison the same concentration of cadmium for C3 sample was established.